Varietal Turnover and Diversity in Banana Production Systems in Uganda - Ajambo, Susan; Erima, Rockefeller; Hakizimana, Desire; Okurut Asher Wilson; Okot, Francis; Omondi, Bonaventure Aman Oduor (not published yet, 2024)
This study investigates varietal turnover dynamics in Ugandan banana farming systems by assessing diversity, examining the adoption and discontinuation rates of recently introduced varieties, and exploring the factors influencing turnover at the farm level. This addresses a critical knowledge gap in understanding the long-term retention and discontinuation factors of the improved varieties. Varietal diversity and turnover were analysed for 399 farmers using the Shannon Diversity Index (H') and the Four-Square Method, along with descriptive statistics to capture farm-level and regional variations. The results demonstrated variations in regional and farm-level banana diversity. Farmers cultivate an average of nine varieties in their fields, and farm-level diversity patterns do not mirror the regional patterns. The Shannon Diversity Index (H=2.006) and Equitability Index (EH=0.450) indicated a moderate variety range, but uneven distribution, with the Eastern and Northern regions exhibiting the highest varietal diversity and evenness. FHIA 17 was the most prevalent improved variety but experienced some decline. Regional variations in varietal turnover exist, with the eastern region leading to the introduction of improved varieties and the central region exhibiting the highest discontinuation rates. The study emphasises local contexts in banana variety management and improvement strategies, highlighting the need for breeding programs that balance agronomic performance with consumer preferences to ensure the sustainable uptake of improved varieties. We recommend implementing a varietal replacement strategy with clear targets and incentives to encourage farmers to adopt improved varieties, improve varietal tracking using digital platforms and surveys to monitor progress and inform decision-making, and strengthen the seed value chain to ensure a sustainable supply of high-quality planting materials.
none
None
Keywords: Banana production systems; Varietal Turnover; Indices; genetic diversity; banana seed system